Оптимизация качества. Сложные продукты и процессы - Калинина Э. В. Элеонора Владимировна; Лапига А. Г. Алла Гавриловна; Поляков В. В. Владимир Валентинович; Хургин Я. И. Яков Исаевич; Вагенкнехт М. Михаэль (Москва, Химия, 1989)
Авт. указаны на обороте тит. л.